(untitled) (Third Sector Social Economic Review, 2025)
This study aims to examine the impact of individuals’ inclusion attitudes toward various disadvantaged groups on contextual performance levels within women’s cooperatives. In the research, inclusion is evaluated across five sub-dimensions: individuals with disabilities, immigrants, minorities, LGBT+ individuals, and individuals with mental health disorders. Utilizing a quantitative research design, the study employed the Turkish adaptation of the Workplace Inclusion Questionnaire developed by Sveinsdottir et al. (2022) as the data collection tool. Data were gathered from 164 members of women’s cooperatives operating in different provinces of Turkey. Correlation analyses revealed a positive and significant relationship between overall inclusion levels and contextual performance. Regression analysis results indicated that overall inclusivity is a significant predictor of contextual performance (R² = .231, p < .001). In light of these findings, the study demonstrates that inclusion attitudes in women’s cooperatives significantly predict contextual performance, and this relationship varies depending on the disadvantaged group. Specifically, inclusion attitudes toward minority groups and individuals with disabilities are higher, whereas inclusion attitudes toward immigrants, LGBT+ individuals, and individuals with mental health disorders are lower. Accordingly, it is recommended to promote inclusion-based practices and develop an inclusive organizational culture within women’s cooperatives.